Biosafety in Modern Laboratories: Standards and Challenges - Mansour Tayeh Maslet Ashammari,; Turky Saud Saad Altamimi,; Khalil Awadh Khalil Alshammari,; Fahad Mohammed Ibrahim Alateeq,; Faris Zamel Saleh Alserheed,; Saleh Mohammed Ibrahim Alateeq,; Munif hamood alshammary,; Naif Abdulmohsen Mubarak Alsaifi, (International Journal of Medical Toxicology and Legal Medicine, 2024)
Introduction: Biosafety in the modern laboratories is an important concept developed to guide handling, storage, and management of biological materials that can cause harm to people or the environment or the researchers. Due to advancement in technology, enhanced biotechnology, improved microbiology and molecular biology laboratories are now involved in research with more advanced topics involving pathogens and new biohazards. These anti-social relations of production mean that biosafety must be maintained to manage risks whilst accommodating research. Aim of work: To explore the significance of biosafety in modern laboratories by examining established standards, identifying the challenges in their implementation, and analyzing the impact of emerging technologies and ethical considerations. Methods: We conducted a comprehensive search in the MEDLINE database's electronic literature using the following search terms: Biosafety, Modern, Laboratories, Standards and Challenges. The search was restricted to publications from 2016to 2024 in order to locate relevant content. We performed a search on Google Scholar to locate and examine academic papers that pertain to my subject matter. The selection of articles was impacted by certain criteria for inclusion. Results: The publications analyzed in this study encompassed from 2016 to 2024. The study was structured into various sections with specific headings in the discussion section. Conclusion:Biosafety in modern laboratories is a cornerstone of scientific research, ensuring that the pursuit of knowledge does not come at the cost of human health or environmental safety. While significant progress has been made in developing biosafety standards and protocols, challenges persist in their implementation. Financial constraints, human behavior, evolving threats, and ethical dilemmas require continuous efforts to improve safety practices. Emerging technologies and the increasing complexity of biological research demand adaptive and forward-looking approaches to biosafety. By fostering a culture of safety, investing in infrastructure, and enhancing global collaboration, the scientific community can mitigate risks while advancing the frontiers of knowledge. Biosafety is not just a regulatory requirement—it is a shared responsibility that underpins the integrity and sustainability of modern science.